Impaired thyroid hormone sensitivity is associated with the degrees of fatty infiltration in metabolic dysfunction associated steatotic liver disease - Li, Ying; Wang, Fang (Frontiers in Endocrinology, 2025)
BackgroundAs a chronic disease, MASLD seriously endangers human health and has a complex pathogenesis. Thyroid hormones (THs) play significant roles in this process. We aimed to analyze the correlation between TH sensitivity and the degrees of fatty infiltration in MASLD.MethodsWe conducted a retrospective study on a sample of 13,144 individuals who underwent physical examinations. Thyroid function, liver and kidney function, blood lipids, and glucose were measured using chemiluminescence methods. TH sensitivity indexes, including free triiodothyronine to free thyroxine ratio (FT3/FT4), thyroid feedback quantile-based index (TFQI), thyroid-stimulating hormone index (TSHI), and thyrotropin thyroxine resistance index (TT4RI), were calculated. The degree of liver fatty infiltration [controlled attenuation parameter (CAP)] was determined by liver shear wave quantification ultrasonography. We then conducted statistical analyses of the above data.ResultsFT3/FT4, TFQI, TSHI, and TT4RI showed significantly increasing trends with the rise of CAP levels (p < 0.001). In males, high CAP levels of CAP were negatively correlated with FT3/FT4 (β [95% CI]: −0.005 [−0.008, −0.002]; p = 0.0004) but positively correlated with TSHI (β [95% CI]: 0.019 [0.002, 0.036]; p = 0.0248) and TFQI (β [95% CI]: 0.015 [0.003, 0.027]; p = 0.01371). In the BMI <28 kg/m² group, low CAP levels of CAP were positively correlated with FT3/FT4 (β [95% CI]: 0.002 [0.002, 0.003]; p < 0.00001), while high CAP levels of CAP were positively correlated with TFQI (β [95% CI]: 0.016 [0.000, 0.031]; p = 0.04805).ConclusionsTH sensitivity is significantly impaired in MASLD. This phenomenon is more pronounced in males and in individuals with BMI <28 kg/m².